Door lock alert system / Norin Azmiah Ahmad - Ahmad, Norin Azmiah (2006)
This project is a breakthrough in technology, which provides significance toward preventing housebreaking crimes that used to be happening around home areas. The project’s scope is focusing on to develop a product that could help reducing the crimes that caused by the carelessness and lack of motivation to verify the safety of the house among the owner of a house. The project is an electronic based project, which is called as a Door Lock Alert System Prototype (DLAS). A modified electric circuit built into an entry way. The project is an optional product for home security, its functions is to motivate the users to verify the safety of the door by making noise, besides the others features that is provided in this products for example is the burglar alarm circuit that is connected to the switch which is will detect the act of intrusion. Such as the movements of the door while the system is activated. Due to the significant of the project that is focusing on to develop a tool that can help to reduce the carelessness amongst users. A survey was conducted to verify whether the project is possible to be developed or in other word, to ensure the objective to develop a tool that can help to reduce carelessness is achieved, and to verify the acceptance of public of this project. Some survey and analysis was conducted. The survey involves the distribution of questionnaires, the questionnaires covers the significant of developing the project.